2018
DOI: 10.3389/fphys.2018.00657
|View full text |Cite
|
Sign up to set email alerts
|

ADM Scaffolds Generate a Pro-regenerative Microenvironment During Full-Thickness Cutaneous Wound Healing Through M2 Macrophage Polarization via Lamtor1

Abstract: Adult mammalian skin has a defective regenerative capacity following full-thickness cutaneous injury; this defect overshadows the complete physiological functions of the skin. Immune-mediated skin reconstruction driven by biological scaffolds is a recently developed innovative repair strategy to support regenerative wound healing. However, to date, little is known about how biological scaffolds orchestrate the immune response to promote regeneration. Here, using acellular dermal matrix (ADM) scaffolds, we disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…The decellularized dermal scaffold (DDS) is a skin tissue that removes cellular components and retains the ECM structure, which was shown to play a therapeutic role in wound repair (183). DDS in particular can regulate the transition of macrophages from the M1 pro-inflammatory phenotype to the M2 pro-repairing phenotype, thus promoting macrophage polarization (184,185). He et al suggested that amino acids produced by collagen degradation in DDS activated the acidsensing pathway in macrophages and induced fate transition (184).…”
Section: Immunomodulatory Biomaterials-based Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The decellularized dermal scaffold (DDS) is a skin tissue that removes cellular components and retains the ECM structure, which was shown to play a therapeutic role in wound repair (183). DDS in particular can regulate the transition of macrophages from the M1 pro-inflammatory phenotype to the M2 pro-repairing phenotype, thus promoting macrophage polarization (184,185). He et al suggested that amino acids produced by collagen degradation in DDS activated the acidsensing pathway in macrophages and induced fate transition (184).…”
Section: Immunomodulatory Biomaterials-based Approachmentioning
confidence: 99%
“…DDS in particular can regulate the transition of macrophages from the M1 pro-inflammatory phenotype to the M2 pro-repairing phenotype, thus promoting macrophage polarization (184,185). He et al suggested that amino acids produced by collagen degradation in DDS activated the acidsensing pathway in macrophages and induced fate transition (184). Further, the inherent components of the ECM, such as hyaluronic acid (HA), or the analogues of the ECM including chitosan, influence the M1-to-M2 phenotype switching (185,186).…”
Section: Immunomodulatory Biomaterials-based Approachmentioning
confidence: 99%
“…ECM-derived tissue engineering biomaterials, unlike their synthetic counterparts, have been shown to prompt unique and constructive tissue remodeling ( Sadtler et al, 2019 ). ECM has an immunomodulatory effect, particularly in terms of regulating macrophages–the key regulator and effector cells in the host response to biomaterials ( Slivka et al, 2014 ; He et al, 2018 ). The phenotypical response of macrophages is a key factor in determining the outcome of downstream tissue remodeling ( Brown et al, 2012b ).…”
Section: Role Of Macrophages In Ecm-mediated Tissue Regenerationmentioning
confidence: 99%
“…Related to these findings, cultured macrophages treated with a mixture of solubilized ECM molecules isolated from either porcine small intestine or urinary bladder led to overexpression of M2 macrophage markers CD206, TGM2, fizz-1 and arg1 [ 130 ]. This is supported by further studies demonstrating that generation of M2-type macrophages is promoted by the degradation products of ECMs from a range of different organs [ 8 , 131 , 132 ]. Decellurised dermal matrices for example, promoted the development of Relmα and Arg1-expressing, M2 macrophages characterised by the production of wound healing factors, including MMPs, and growth factors responsible for angiogenesis and ECM remodeling [ 132 ].…”
Section: Ecm Regulation Of Immune Cell Functionmentioning
confidence: 65%